THE EFFECT OF THE COMBINATION OF BAY LEAVES (Syzygium polyanthum) AND BREADFRUIT LEAVES (Artocarpus altilis) ON CHOLESTEROL LEVELS IN HYPERCHOLESTEROLEMIC MICE - Sapitri, Nabila; Lestariningsih, Nanik; Indahsari, Lilin Ika Nur (Universitas Medan Area, 2025)
Central Kalimantan has enormous natural resource potential, particularly in the area of medicinal plants such as bay leaves and breadfruit. Although, people in Central Kalimantan have utilized herbs as medicine, there has not been any scientific study done. This study aims to determine the effect of giving a combination of bay leaf and breadfruit leaf extracts in reducing cholesterol levels in Balb/c Hypercholesterolaemia mice. This study was conducted using the Mixed Method method, namely exploratory research and experimental research. The research subjects used were 28 female Balb/c mice in Hypercholesterolaemia conditions. In this study there were 7 treatments including positive control, negative control, P1 (20)%, P2 (30)%, P3 (40)%, P4 (50)%, P5 (60)% with 4 replications. The data analysis technique used in this study was One Way ANOVA. The finding of the study indicate that the combination of Bay Leaves and Breadfruit Leaves has an effect on reducing cholesterol levels in hypercholesterolemic mice, which can be seen from the p-value α (α 0.05) which is 0.000. Additionally, the most effective concentration in reducing cholesterol levels in hypercholesterolemic mice resulting in the concentration of P6 (50%) with a decrease of 60.25 Mg/dL.